英國、臺灣、馬來西亞戶外冒險教育發展之 比較分析 A Comparative Analysis on Outdoor Adventure Education Development in England, Taiwan, and Malaysia - 李晟瑋 Cheng-Wei Li; 葉優寧 Evelyn Yeap Ewe Lin (Journal of Research in Education Sciences)
戶外冒險教育作為一個教育哲學，在不同國家有著不同的發展脈絡與實踐。本研究聚焦在三個國家的教育系統，進行戶外冒險教育發展和實施的探究，旨在協助戶外冒險教育的發展與推動，透過文件分析的方式，比較分析英格蘭、臺灣和馬來西亞學校課程的演變與教育發展。本研究採用P. Bourdieu實踐理論（theory of practice）中的習性、場域和資本概念，協助研究者在不同的社會與教育背景下探究其教育發展。本研究藉由四個主題—「立法和指導」、 「課程安排」、「教育規範與價值觀」與「戶外冒險教育的態度」，探討其學校教育與高等教育之相似性與相異處。結果發現戶外冒險教育的發展在學校教育與高等教育間未存在連貫性。此外，本研究亦指出，馬來西亞教育部有必要以更全面的方式重新審視戶外冒險教育在學校教育的實施。總而言之，本研究強調在不同教育系統中發展戶外冒險教育時應考慮文化、社會和政策背景的重要性。 Outdoor Adventure Education (OAE) as an educational philosophy has varying levels of development and practices across different countries. This cross-cultural study explored the development and interpretation of OAE in academic systems of three countries, namely England, Taiwan, and Malaysia. The goal of this research was to provide insight into the development of OAE profiling measures by comparing the curricula of these countries’ schools. The study was based on document analysis with a comparative cultural perspective. The ideas of habitus, field, and capital articulated by Bourdieu were integrated as major supplements to illustrate the cultural patterns linked to bodily movements. The investigation uncovered both parallels and divergences in the development and conceptualization of OAE within the three nations, and discussed the context in both university and schooling sectors within four generated themes: “legislation and guidance,” “curriculum arrangement,” “pursuit of educational norms and values,” and “attitude toward OAE.” A notable disconnection between schools and universities regarding OAE initiatives was observed in Malaysia. Additionally, the study highlighted the significance of considering cultural, societal, and policy contexts in shaping the landscape of OAE in diverse educational systems. The findings of the study recommend that the Ministry of Education of Malaysia reassess the implementation of OAE in a more holistic manner.